Redesign Geometri Lereng Penambangan Batugamping Kuari C di PT X Kecamatan Palimanan Kabupaten Cirebon Provinsi Jawa Barat - Guntur Indra Prahasta; Yuliadi (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. PT X is a cement producer which has a limestone mine in Palimanan District, Cirebon Regency, West Java Province. In the Quarry C limestone mining area there has been an landslide that has resulted in the inoperation of mining activities in the area. This research was conducted on the slopes of the Quarry C mine which had experienced a landslide. This study aims to determine the causes of landslides that occur, determine the value of cohesion, deep friction angles and safety factors when landslides occur, and recommend safe slope geometry with the input parameters results of back analysis. In this study, to determine the type of avalanche that occurs is done with stereographic projections that refer to the criteria of the landslide Hoek and Bray, 1981. Data taken in the form of strike and discontinuous dip fields using a geological compass. The initial parameter input uses physical property test data to obtain the value of natural density and mechanical properties testing, namely the shear strength test to obtain the value of cohesion and deep friction angle, as well as the compressive strength test to get the modulus young and poisson ratio values. To find out the value of cohesion, the friction angle in the safety factor during a landslide is performed back analysis using the probability method. Based on the results of data processing and data analysis conducted, it can be concluded that the landslides that occurred in section C1 to section C3 were in the form of arc slides. The results of back analysis of landslides in sections C1 through section C3 are in the form of cohesion and friction angle during landslides, namely for claystone lithology (c = 129.3 kPa, Ø = 25.04o) and for Marly Limestone lithology (c = 80.17 kPa, Ø = 11.23o). For the recommended slope geometry in section C1 is α = 8 o, H = 37.265 m with FK = 1,299 and section C2 is α = 10 o, H = 44.712 m with FK = 1,313. Abstrak. PT X adalah salah satu produsen semen yang mempunyai tambang batugamping di Kecamatan Palimanan, Kabupaten Cirebon, Provinsi Jawa Barat. Pada area penambangan batugamping Kuari C telah terjadi longsoran yang mengakibatkan tidak bisa beroperasinya kegiatan penambangan di area tersebut. Penelitian ini bertujuan untuk mengetahui penyebab kelongsoran yang terjadi, mengetahui nilai kohesi, sudut gesek dalam dan faktor keamanan saat terjadi longsor, serta merekomendasikan geometri lereng yang aman dengan input parameter hasil analisis balik. Pada penelitian ini, untuk mengetahui jenis longsoran yang terjadi dilakukan dengan proyeksi stereografi yang mengacu pada kriteria longsoran Hoek and Bray, 1981. Data yang diambil berupa strike dan dip bidang diskontinu menggunakan kompas geologi. Input parameter awal menggunakan data hasil pengujian sifat fisik untuk mendapatkan nilai natural density dan pengujian sifat mekanik yaitu uji kuat geser untuk mendapatkan nilai kohesi dan sudut gesek dalam, serta uji kuat tekan untuk mendapatkan nilai modulus young dan poisson ratio. Untuk mengetahui nilai kohesi, sudut gesek dalam faktor keamanan saat terjadi longsor dilakukan analisis balik dengan metode probabilitas. Berdasarkan hasil pengolahan data dan analisis data yang dilakukan, dapat disimpulkan bahwa longsoran yang terjadi pada section C1 sampai dengan section C3 berupa longsoran busur. Hasil analisis balik kelongsoran di section C1 sampai dengan section C3 berupa nilai kohesi dan sudut gesek dalam saat terjadi longsor, yaitu untuk litologi claystone (c = 129.3 kPa, Ø = 25.04o) dan untuk litologi Marly Limestone (c = 80.17 kPa, Ø = 11.23o). Untuk geometri lereng yang direkomendasikan pada section C1 adalah α = 8 o, H = 37.265 m dengan FK = 1,299 dan section C2 adalah α = 10 o, H = 44.712 m dengan FK = 1,313.